The Effect of Project-Based Learning on Students Collaborative Skills and Learning Outcomes on Virus Material - Azira Azira; Marlinda Nilan Sari Rangkuti (Biocaster : Jurnal Kajian Biologi, 2026)
This study aims to determine the effect of Project-Based Learning (PjBL) on students' collaboration skills and cognitive learning outcomes in biology, specifically on virus topics, among 10th grade students at SMA Negeri 1 Tanjungtiram. A quasi-experimental design with a pretest-posttest control group was employed, involving 72 students from two classes selected through random sampling. The experimental class implemented PjBL, while the control class used conventional learning. Collaboration skills were measured using observation sheets, and cognitive learning outcomes were assessed using multiple-choice tests. The results showed that the experimental class achieved a mean collaboration skill score of 84.66% (very skilled category), significantly higher than the control class at 64.05% (skilled category). Cognitive learning outcomes also improved substantially, with the experimental class reaching an N-gain of 0.72 (high category) compared to 0.46 (medium category) in the control class. Mann-Whitney U test results confirmed a significant effect of PjBL on both variables (p < 0.05). These findings suggest that PjBL is an effective instructional model for developing students' collaboration skills and improving their learning outcomes in biology, particularly on virus topics.